Leptin-induced transphosphorylation of vascular endothelial growth factor receptor increases Notch and stimulates endothelial cell angiogenic transformation. (October 2016) - Lanier, Viola; Gillespie, Corey; Leffers, Merle; Daley-Brown, Danielle; Milner, Joy; Lipsey, Crystal; Webb, Nia; Anderson, Leonard M.; Newman, Gale; Waltenberger, Johannes; Gonzalez-Perez, Ruben Rene
Abstract: Leptin increases vascular endothelial growth factor (VEGF), VEGF receptor-2 (VEGFR-2), and Notch expression in cancer cells, and transphosphorylates VEGFR-2 in endothelial cells. However, the mechanisms involved in leptin's actions in endothelial cells are not completely known. Here we investigated whether a leptin-VEGFR-Notch axis is involved in these leptin's actions. To this end, human umbilical vein and porcine aortic endothelial cells (wild type and genetically modified to overexpress VEGFR-1 or -2) were cultured in the absence of VEGF and treated with leptin and inhibitors of Notch (gamma-secretase inhibitors: DAPT and S2188, and silencing RNA), VEGFR (kinase inhibitor: SU5416, and silencing RNA) and leptin receptor, OB-R (pegylated leptin peptide receptor antagonist 2: PEG-LPrA2). Interestingly, in the absence of VEGF, leptin induced the expression of several components of Notch signaling pathway in endothelial cells. Inhibition of VEGFR and Notch signaling significantly decreased leptin-induced S-phase progression, proliferation, and tube formation in endothelial cells. Moreover, leptin/OB-R induced transphosphorylation of VEGFR-1 and VEGFR-2 was essential for leptin's effects. These results unveil for the first time a novel mechanism by which leptin could induce angiogenic features via upregulation/trans-activation of VEGFR and downstream expression/activation of Notch in endothelial cells. Thus, high levels of leptin found in overweight and obese patients might lead to increased angiogenesis by activating VEGFR-Notch signaling crosstalk in endothelial cells. These observations might be highly relevant for obese patients with cancer, where leptin/VEGFR/Notch crosstalk could play an important role in cancer growth, and could be a new target for the control of tumor angiogenesis.